Myocardial Injury after Noncardiac Surgery: A Case Report of Acute Chest Pain and Elevated Troponin Levels, Challenges and Management Strategies - Ton, Yori Yarson; Anggraeni, Novita; Irawan, Dino; Hidayat, Nopian (JAI (Jurnal Anestesiologi Indonesia), 2025)
Background: Perioperative myocardial injury is a common complication following noncardiac surgery, linked to significant morbidity and mortality. With over 300 million surgeries performed worldwide annually, this number has increased by more than 100 million in the past two decades.Case: A 42-year-old woman underwent elective craniotomy for a right cerebellar hemangioblastoma and was admitted to the intensive care unit (ICU) postoperatively. On day three, she developed typical chest pain, inferior ST-elevation myocardial infarction (STEMI), and cardiogenic shock. Her medical history included the use of euthyrox following a total thyroidectomy 15 years prior, with no prior cardiac issues. Upon examination, she was conscious but had low blood pressure (58/41 mmHg), an elevated heart rate (103 bpm), and cold extremities. Her troponin I level was elevated at 9383.0 ng/mL. The diagnosis was major postoperative myocardial infarction.Therapy: The patient received aspirin, atorvastatin, heparin, norepinephrine, and dobutamine for shock management, with close hemodynamic monitoring. By day six, her condition improved, and her electrocardiogram (ECG) was normal. By day nine, she was transferred to the high care unit.Discussion: Myocardial injury after noncardiac surgery (MINS) includes both myocardial infarction and ischemic myocardial injury, which may not meet the Universal Definition of Myocardial Infarction. MINS usually occurs within 30 days of surgery, especially within the first 72 hours. Its causes are multifactorial, including plaque rupture, oxygen supply-demand imbalance, arrhythmias, and pulmonary embolism. Studies suggest that cardiovascular therapy, including aspirin and statins, is effective. Aspirin reduces 30-day mortality, while statins offer long-term benefits through anti-inflammatory effects. Low-dose aspirin, statins, and Renin-Angiotensin System inhibitors are recommended.Conclusion: MINS is a serious postoperative complication, even in patients without a history of cardiovascular disease, as demonstrated in this case. Prompt recognition and appropriate therapy with aspirin, heparin, and statins, along with close monitoring, can lead to significant clinical improvement.